Association of Short-term Heart Rate Variability and Sudden Unexpected Death in Epilepsy. (14th December 2021) - Sivathamboo, Shobi; Friedman, Daniel; Laze, Juliana; Nightscales, Russell; Chen, Zhibin; Kuhlmann, Levin; Devore, Sasha; Macefield, Vaughan; Kwan, Patrick; D'Souza, Wendyl; Berkovic, Samuel F.; Perucca, Piero; et al.
Abstract : Background and Objectives: We compared heart rate variability (HRV) in sudden unexpected death in epilepsy (SUDEP) cases and living epilepsy controls. Methods: This international, multicenter, retrospective, nested case–control study examined patients admitted for video-EEG monitoring (VEM) between January 1, 2003, and December 31, 2014, and subsequently died of SUDEP. Time domain and frequency domain components were extracted from 5-minute interictal ECG recordings during sleep and wakefulness from SUDEP cases and controls. Results: We identified 31 SUDEP cases and 56 controls. Normalized low-frequency power (LFP) during wakefulness was lower in SUDEP cases (median 42.5, interquartile range [IQR] 32.6–52.6) than epilepsy controls (55.5, IQR 40.7–68.9; p = 0.015, critical value = 0.025). In the multivariable model, normalized LFP was lower in SUDEP cases compared to controls (contrast −11.01, 95% confidence interval [CI] −20.29 to 1.73; p = 0.020, critical value = 0.025). There was a negative correlation between LFP and the latency to SUDEP, where each 1% incremental reduction in normalized LFP conferred a 2.7% decrease in the latency to SUDEP (95% CI 0.95–0.995; p = 0.017, critical value = 0.025). Increased survival duration from VEM to SUDEP was associated with higher normalized high-frequency power (HFP; p = 0.002, critical value = 0.025). The survival model with normalized LFP was associated with SUDEP ( c statistic 0.66, 95% CI 0.55–0.77), which nonsignificantly increased with the addition of normalized HFP ( c statistic 0.70, 95% CI 0.59–0.81; p = 0.209). Conclusions: Reduced short-term LFP, which is a validated biomarker for sudden death, was associated with SUDEP. Increased HFP was associated with longer survival and may be cardioprotective in SUDEP. HRV quantification may help stratify individual SUDEP risk. Classification of Evidence: This study provides Class III evidence that in patients with epilepsy, some measures of HRV are associated with SUDEP.